تأثير استراتيجية التعلم النشط "الدرس الأقراني" في تعليم النحو في الصف الثامن للمدرسة التربية الإسلامية كامانج موديك أغام - Safreni, Junia; Rahmawati, Rahmawati; Ritonga, Mahyudin (YASIN, 2025)
The research question addressed in this study is: Does the peer lesson strategy influence the learning of nahwu (Arabic grammar) in the eighth-grade class at Pondok Pesantren Tarbiyah Islamiyah Kamang Mudik, Agam? This study aims to assess students' abilities in learning nahwu prior to the implementation of the peer lesson strategy, to explain the strategy's implementation, and to evaluate its impact on improving learning outcomes. This research employs a quantitative field method using a quasi-experimental design with a nonequivalent control group design model. Data collection methods include observation, testing, and documentation. Hypothesis testing was conducted using SPSS version 26. The first finding reveals that students’ initial nahwu skills were weak (da'if), with average scores of 51.76 in the control group and 48.23 in the experimental group. The second finding shows that the peer lesson strategy was implemented in three phases: introduction, main activity, and conclusion—with a good overall rating. After the strategy was applied, the control group’s average increased to 61.17 (still da'if), while the experimental group’s average rose significantly to 81.76, rated as good. Hypothesis testing yielded a value of 11.191 with a 2-tailed significance level of 0.05, indicating a statistically significant effect of the peer lesson strategy on nahwu learning.